'The fable of the Bs': between substantialism and deep relational thinking about power. Issue 2 (3rd May 2016) - Selg, Peeter
Abstract : The paper aims at drawing out concisely the differences and potentials for a dialogue between the two major understandings of relational approach to power, that the author dubs 'the fable of the Bs' and 'trans-actionalism'. Compared to traditional substantialist approaches that overwhelmingly focus on the As (the powerful) 'the fable of the Bs' highlights the importance also of considering the contribution of the Bs (the powerless) in creating and upholding power relations. 'Trans-actionalism' or 'deep relational thinking' presumes the primacy of relations over entities. The elements of power relations are viewed not as being 'given' prior to those relations, but as being constituted within them.